-5+3(3+4x)=5(3x-7)

Simple and best practice solution for -5+3(3+4x)=5(3x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5+3(3+4x)=5(3x-7) equation:


Simplifying
-5 + 3(3 + 4x) = 5(3x + -7)
-5 + (3 * 3 + 4x * 3) = 5(3x + -7)
-5 + (9 + 12x) = 5(3x + -7)

Combine like terms: -5 + 9 = 4
4 + 12x = 5(3x + -7)

Reorder the terms:
4 + 12x = 5(-7 + 3x)
4 + 12x = (-7 * 5 + 3x * 5)
4 + 12x = (-35 + 15x)

Solving
4 + 12x = -35 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
4 + 12x + -15x = -35 + 15x + -15x

Combine like terms: 12x + -15x = -3x
4 + -3x = -35 + 15x + -15x

Combine like terms: 15x + -15x = 0
4 + -3x = -35 + 0
4 + -3x = -35

Add '-4' to each side of the equation.
4 + -4 + -3x = -35 + -4

Combine like terms: 4 + -4 = 0
0 + -3x = -35 + -4
-3x = -35 + -4

Combine like terms: -35 + -4 = -39
-3x = -39

Divide each side by '-3'.
x = 13

Simplifying
x = 13

See similar equations:

| 4p^2-12p-16=0 | | -5=0.6x+3 | | 3-4(x+2)=2x+7 | | -49-2x=6x+6 | | 5x+3(x+6)=25+8x | | -5=4+3x | | 42=2d+6 | | x^3=2x^2+24x | | -120=42b-120-76b | | -5-8m=5-6(m+3) | | 9-3-6=0 | | 5-8x=116-29x | | -7(1+8a)=385 | | -4(6n-8)+n=55 | | 4[2p-4(p+5)]=25 | | -3n-10=-34 | | y=2(2+1)+5(3+2) | | (X^3)-5X+7=19 | | (6-3x)8=192 | | 24k+33=12k+18-12k+35 | | -5(1-4x)=135 | | -11p=-99 | | 9y=8(y+15) | | 2(-8n-4)-4=-5(1+3n) | | 15w-19w=36 | | 10x^2-2x+34=0 | | 6m-(5-9m)=12 | | 2(x-3)=3x-5 | | 3(6-4x-2x)+8(3x+4)=14 | | -11+2r-3r=r+5 | | 2x^2+7=20 | | 4x-8x+2=x-9+11 |

Equations solver categories